The collaborative learning development exercise (CLeD-EX): an educational instrument to promote key collaborative learning behaviours in medical students - Maha Pervaz Iqbal; Gary M. Velan; Anthony J. O’Sullivan; Chinthaka Balasooriya (BMC Medical Education, 2020)
Abstract Background Modern clinical practice increasingly relies on collaborative and team-based approaches to care. Regulatory bodies in medical education emphasise the need to develop collaboration and teamwork competencies and highlight the need to do so from an early stage of medical training. In undergraduate medical education, the focus is usually on collaborative learning, associated with feedback and reflection on this learning This article describes a novel educational instrument, the Collaborative Learning Development Exercise (CLeD-EX), which aims to foster the development of key collaborative learning competencies in medical students. In this article we report on the effectiveness, feasibility and educational impact of the CLeD-EX. Methods In this study, the “educational design research” framework was used to develop, implement and evaluate the CLeD-EX. This involved adopting a systematic approach towards designing a creative and innovative instrument which would help solve a real-world challenge in developing collaborative learning skills. The systematic approach involved a qualitative exploration of key collaborative learning behaviours which are influential in effective collaborative learning contexts. The identified competencies were employed in the design of the CLeD-EX. The design of the CLeD-EX included features to facilitate structured feedback by tutors to students, complemented by self-evaluation and reflection. The CLeD-EX was field-tested with volunteer junior medical students, using a controlled pre-test post-test design. Analysis of the completed CLeD-EX forms, self-perception surveys (i.e. pre-test and post-test surveys) and analyses of reflective reports were used to explore the educational impact of CLeD-EX, as well as its utility and practicality. Results After using the CLeD-EX, students showed a significant improvement in critical thinking and group process as measured by a previously validated instrument. Both students and tutors recognised CLeD-EX as an effective instrument, especially as a structured basis for giving and receiving feedback and for completing the feedback loop. CLeD-EX was also found to be feasible, practical and focused, while promoting learning and effective interactions in small group learning. Conclusion The findings of this study support the introduction of an effective and feasible educational instrument such as the CLeD-EX, to facilitate the development of students’ skills in collaborative learning.